Monitoring Stray Natural Gas in Groundwater With Dissolved Nitrogen. An Example From Parker County, Texas. Issue 9 (5th September 2018) - Larson, Toti E.; Nicot, Jean‐Philippe; Mickler, Patrick; Castro, M. Clara; Darvari, Roxana; Wen, Tao; Hall, Chris M.
Abstract: Concern that hydraulic fracturing and natural gas production contaminates groundwater requires techniques to attribute and estimate methane flux. Although dissolved alkane and noble gas chemistry may distinguish thermogenic and microbial methane, low solubility and concentration of methane in atmosphere‐equilibrated groundwater precludes the use of methane to differentiate locations affected by high and low flux of stray methane. We present a method to estimate stray gas infiltration into groundwater using dissolved nitrogen. Due to the high concentration of nitrogen in atmospheric‐recharged groundwater and low concentration in natural gas, dissolved nitrogen in groundwater is much less sensitive to change than dissolved methane and may differentiate groundwater affected high and low flux of stray natural gas. We report alkane and nitrogen chemistry from shallow groundwater wells and eight natural gas production wells in the Barnett Shale footprint to attribute methane and estimate mixing ratios of thermogenic natural gas to groundwater. Most groundwater wells have trace to nondetect concentrations of methane. A cluster of groundwater wells have greater than 10 mg/L dissolved methane concentrations with alkane chemistries similar to natural gas from the Barnett Shale and/or shallower Strawn Group suggesting that localized migration of natural gas occurred. Two‐component mixing models constructed with dissolved nitrogen concentrations and isotope values identify three wells that were likely affected by a large influx of natural gas with gas:water mixing ratios approaching 1:5. Most groundwater wells, even those with greater than 10‐mg/L methane, have dissolved nitrogen chemistry typical of atmosphere‐equilibrated groundwater suggesting natural gas:water mixing ratios smaller than 1:20. Plain Language Summary: Hydraulic fracturing, horizontal drilling, and associated natural gas production have dramatically changed the energy landscape across America over the past 10 years. Along with this renaissance in the energy sector has come public concern that hydraulic fracturing may contaminate groundwater. In this study we measure the chemistry of dissolved gas from shallow groundwater wells located above the Barnett Shale natural gas play, a tight gas reservoir located west of the Dallas‐Fort Worth Metroplex. We compare groundwater chemistry results to natural gas chemistry results from nearby production wells. Most groundwater wells have trace to nondetectible concentrations of methane, consistent with no measurable infiltration of natural gas into shallow groundwater. A cluster of groundwater wells have greater than 10 mg/L dissolved methane concentrations with alkane chemistries similar to natural gas. Using dissolved nitrogen and alkane concentrations and their stable isotope ratios in combination with chemical mixing models, we conclude that natural gas transported from the shallower Strawn Group affected these groundwater wells rather than natural gas from the deeper Barnett Shale, which is the target of hydraulic fracturing in this area. These results suggest that hydraulic fracturing has not affected shallow groundwater drinking sources in this area. Key Points: Dissolved nitrogen in groundwater provides a means to differentiate high‐ and low‐flux infiltration of stray gas Nitrogen concentrations and isotope values may attribute natural gas sources